Histological subtype of renal cell carcinoma significantly affects survival in the era of partial nephrectomy - Nguyen, Daniel P.; Vertosick, Emily A.; Corradi, Renato B.; Vilaseca, Antoni; Benfante, Nicole E.; Touijer, Karim A.; Sjoberg, Daniel D.; Russo, Paul (Urologic oncology, 2016)
To analyze whether the histological subtype of renal cell carcinoma (RCC) affects survival after surgical resection in contemporary patients, and if so, whether prognostic significance differs according to the type of surgical resection or tumor stage. From 2006 to 2014, 2,237 patients underwent surgical resection (25% radical nephrectomy and 75% partial nephrectomy [PN]) for nonmetastatic RCC at a tertiary referral center. Estimated survival function curves and Cox regression models evaluated the effect of histological subtype on recurrence-free survival (RFS) and overall survival (OS). Interaction analyses tested whether the effect of histological subtype depends on the type of surgical resection or tumor stage. Patients with RCC stage T2 or lower and those with low-grade conventional clear cell, papillary or chromophobe RCC of any stage had 5-year RFS probabilities>90%. Patients with clear cell papillary RCC stage T3 or greater had predicted 5-year RFS of 81%. However, 5-year OS probabilities were>94% for clear cell papillary RCC of any stage. High-grade conventional clear cell and papillary RCC stage T2 or lower, low-grade conventional clear cell and chromophobe RCC of any stage conferred 5-year OS probabilities of >93%. Unclassified RCC demonstrated the lowest OS probabilities at any stage. In multivariable analyses, histological subtype affected RFS (P<0.0001) and OS (P = 0.026) following surgical resection, with no differences in this association for radical nephrectomy vs. PN (RFS, P = 0.2; OS, P = 0.4), and across pathologic stages (RFS, P = 0.1; OS, P = 0.3). Compared with low-grade conventional clear cell RCC, chromophobe (hazard ratio [HR] = 0.72, 95% CI: 0.30–1.75) and papillary RCC (HR = 0.30, 95% CI: 0.09–0.97) conferred lower risk of recurrence. Chromophobe (HR = 0.67, 95% CI: 0.30–1.52) and clear cell papillary RCC (HR = 0.91, 95% CI: 0.12–6.78) conferred the lowest risk of all-cause mortality. In the era of PN for RCC, histological subtype remained a significant predictor of survival, regardless of type of surgical resection or tumor stage. •The histological subtype of renal cell carcinoma remains a predictor of survival.•The predictive value of histological subtype is independent of the surgical technique.•The predictive value of histological subtype is independent of the pathologic stage.